Massive resistance : southern opposition to the second reconstruction - Webb, Clive, 1970- (Oxford University Press, 2005)
Ten essays discuss southern white resistance on school segregation and other civil rights issues from the perspectives of gender studies, the Cold War, religion & theology, private education, the events in Little Rock & the intellectual foundations of massive resistance.